The Impact of Implementing an Inquiry-Based Learning Model with Pop-Up Book Media on the Academic Performance of Elementary School Students - Aulia Rohmawati (Indonesian Journal of Innovative Teaching and Learning, 2024)
The purpose of this study was to determine whether there is an effect of using the inquiry learning model using Pop-Up Book media on student learning outcomes at SD Islam AL Falih Kediri City. This type of research uses a quasi-experimental approach. The research method used a pretest-posttest control group design. The research sample amounted to 36 students. The results of the study obtained the findings of the learning outcomes of Science IV grade students who were taught by using the inquiry model better than students who were taught without using the inquiry model. The conclusion of the research is obtained in the context of using learning methods in the classroom, inquiry media can be used as a teaching and learning method. The contribution of the results of this study as novelty and scientific information related to the role and influence of inquiry learning models using Pop-Up Book media on student learning outcomes in schools.